Upaya Pembentukan Karakter Pemuda melalui Pendidikan di Tajaul Karomah Desa Situgadung Kabupaten Tangerang - Ariyanti, Eti; Wardani, Endang Susilo; Irawati, Laila (Jurnal PKM Manajemen Bisnis, 2025)
The rapid development of technology and information in today's era poses significant challenges for youth, particularly in shaping strong character and moral values. Responding to this issue, the Community Service Program (PKM) titled "Efforts to Build Youth Character through Education at Tajaul Karomah, Situgadung Village, Tangerang Regency" was conducted to instill positive character values among students and educators. The main objective of this PKM activity was to strengthen the moral foundation and personal development of the youth through educational approaches and interactive learning methods. The activity was carried out on May 4, 2025, at the Tajaul Karomah Educational Institution Hall in Situgadung Village. It involved 15 lecturers from Pamulang University as facilitators and 45 participants consisting of students and teachers from Tajaul Karomah. The implementation method included material presentations, simulations, group discussions, and Q&A sessions. The PKM process was divided into three main stages: preparation, implementation, and reporting. The results of the activity showed increased awareness among participants regarding the importance of character education, better understanding of values such as discipline, responsibility, and respect, as well as improved interaction between educators and students. This program effectively supported the educational institution’s mission to cultivate morally sound and socially responsible youth.